Botulinum Toxin, a Drug with Potential Interest for Dentists—An Introduction - Merete Bakke (Toxins, 2022)
The review is an introduction to medical, non-cosmetic treatments with botulinum neurotoxin (BoNT) in the orofacial region. It focuses on the current most common, best-documented and safest indications of interest for dentists in terms of dystonia and sialorrhea. These conditions are recommended to start with and suitable to gain better skill and experience with BoNT. The introduction also stresses the importance of correct diagnostics based on interdisciplinary cooperation, precise targeting of the injections, measurements of treatment effect, and control of the oral health with regard to side effects.